A Comparison Between Functional Results in Intra-Articular Displaced Calcaneus Fractures Managed with Conservative and Operative Treatment: A Randomized Controlled Trial - Farukh Hussain, Ali Muhammad Bhutto, Waseem Ahmed, Hussain Bux Palh, Sijad Ahmed Mahar, Ahmed Raza Laghari, Niaz Hussain Keerio (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To make a comparison between functional results in intra-articular displaced calcaneus fractures which are treated conservatively and operative treatment Study design: A randomized controlled trial Place and Duration:This study was conducted at ward 17 JPMC Karachi from January 20221 to January 2022. Methodology: This study includes 32 individuals who had displaced intra-articular calcaneal fractures. These individuals were classified into two groups, each group with 16 individuals. They were randomly assigned to either operative or conservative treatment. Clinical results, as well as radiological results (Modified Rowe’s score), were assessed at a 1-year follow-up. Results: All results were measured using Modified Rowe’s score. With a 1-year follow-up of the operative group, according to Modified Rowe’s score, 6 individuals had excellent results representing 37.5%, 8 individuals had good results representing 50%, and only 2 individuals had satisfactory results representing 12.5%. On the other hand, with a 1-year follow-up of the conservative group, only 2 individuals had excellent results representing 12.5%, 7 individuals had good results representing 43.75%, 5 individuals had satisfactory results representing 31.25%, and 2 individuals had poor results representing 12.5%. A few challenges were seen in each group. In the operative group, delayed wound healing was a complication seen in 2 cases while in the conservative group, peroneal tendonitis, subtalar arthritis and malunion were seen as a complication. Conclusion: In conclusion, the operative group was seen to be more effective to cure displaced intra-articular calcaneus fractures rather than the comparative group. Only a few complications, better functional recovery, early rehabilitation, and early weight bearing were seen in the operative treatment. Keywords: Calcaneus fractures, functional outcome, rehabilitation, conservative treatment